Red cell distribution width and neutrophil-to-lymphocyte ratio predict left ventricular dysfunction in acute anterior ST-segment elevation myocardial infarction - Karakas, Mustafa Serkan (Journal of the Saudi Heart Association, 2016)
OBJECTIVES: Red cell distribution width (RDW) and neutrophil-to-lymphocyte ratio (NLR) are the two markers used to determine risk of mortality and adverse cardiovascular outcomes in patients with acute myocardial infarction. The relationship between RDW, NLR, and left ventricular (LV) systolic functions has not been reported. In this report, we aimed to investigate the relationship between RDW, NLR, and LV systolic function in anterior ST-segment elevation myocardial infarction (STEMI) patients who underwent primary percutaneous coronary intervention (PCI)